If God is love, don't be a jerk : finding a faith that makes us better humans - Pavlovitz, John (Westminster John Knox Press, 2021)
"John Pavlovitz examines the bedrock ideas of our religion: the existence of hell, the utility of prayer, the way we treat LGBTQ people, the value of anger, and other doctrines to help all of us take a good, honest look at how the beliefs we hold can shape our relationships with God and our fellow humans---and to make sure that love has the last, loudest word"--